Correction: Composition and Expression of Genes Encoding Carbohydrate-Active Enzymes in the Straw-Degrading Mushroom Volvariella volvacea. - Bingzhi Chen (Public Library of Science (PLoS), 2013)
[This corrects the article on p. e58780 in vol. 8.].